2021
DOI: 10.1016/j.aninu.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gut microbiota and host-metabolism: Emphasis on hormones related to reproductive function

Abstract: It has been well recognized that interactions between the gut microbiota and host-metabolism have a proven effect on health. The gut lumen is known for harboring different bacterial communities. Microbial by-products and structural components, which are derived through the gut microbiota, generate a signaling response to maintain homeostasis. Gut microbiota is not only involved in metabolic disorders, but also participates in the regulation of reproductive hormonal function. Bacterial phyla, which are localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 129 publications
1
40
0
Order By: Relevance
“…However, there are limited studies showing this link and more studies are required to further understand this. 54 31 NA ↓ Alpha diversity in women ↔ Beta diversity between groups (observed in a cohort of healthy women and women with PCOM and PCOS)…”
Section: Discussionmentioning
confidence: 99%
“…However, there are limited studies showing this link and more studies are required to further understand this. 54 31 NA ↓ Alpha diversity in women ↔ Beta diversity between groups (observed in a cohort of healthy women and women with PCOM and PCOS)…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ghrelin, obestatin, insulin, and other gut-derived hormones have direct or indirect effects on the reproductive axis and play roles in regulating energy balance and reproductive function [27]. Previous studies have shown that the gut microbiota plays an important role in regulating the reproduction of the host [28,29]. However, there are no related studies that reported the association between the gut microbiota and seasonal breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, some metabolites of tryptophan and indoles turnover decreased after testosterone depletion and were not restored by testosterone. Some of these indoles represent microbial metabolites from tryptophan gut metabolism 49 and the alteration may be the result of the altered steroid profile, several studies indicate that steroids influence the gut microbiome 50,51 .…”
Section: Discussionmentioning
confidence: 99%